KARAKTERISTIK FRUIT LEATHER MANGGA-ROSELA DENGAN KONSENTRASI KARAGENAN BERBEDA - Krismawan, Adi; Pato, Usman (SAGU, 2023)
Making fruit leather needs to be added hydrocolloids to improve plasticity that often occurs, especially in raw materials that contain low pectin, such as mango and rosella. One solution that can be done is to add ingredients that have good plasticizing properties, such as carrageenan. The study aimed to obtain the best concentration of carrageenan in the manufacture of fruit leather. This research was conducted experimentally using a completely randomized design (CRD) consisting of five treatments as follows: without the addition of carregeenan (K0); the addition of carrageenans for 0.3% (K1), 0.6% (K2), 0.9% (K3), and 1.2% (K4). The data obtained were analyzed statistically using analysis of variance (ANOVA), then analyzed with duncan’s multiple range test (DMRT) at 5% level. The results showed that addition of various concentrations of carrageenan significantly affected the moisture, ash, fiber content, total sugar, pH value, descriptive color, and descriptive and hedonic texture of the mango-rosella fruit leather but did not significantly influence the hedonic color, aroma, taste, overall assessment, and descriptive aroma and taste. The best treatment in this study was K1 (addition of 0.3% carrageenan) with moisture content 13.88%, ash 0.37%, fiber 5.16%, total sugar 49.72%, pH value 2.97. The K1 treatment had slightly red color description, has a mango and rosella aroma, a sweet, slightly sour taste, and slighlty chewy texture. The average panelist liked the K1 treatment in terms of color, aroma, taste, texture, and overall value.